Is breath testing without 13C-labelled external urea able to detect Helicobacter pylori infection? - Carlos, Ana Beatriz Marques [UNESP]; de Oliveira, Cássio Vieira [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Costa, Vladimir Eliodoro [UNESP] (Springer Nature, 2019)
Helicobacter pylori (H. pylori) infection is the main cause of gastric inflammation and peptic ulcer disease. Diagnosis and treatment are important to prevent these outcomes. The diagnosis of H. pylori infection can be performed by non-invasive methods, such as 13C-urea breath test (13C-UBT). As endogenous urea is normally released to body cavities, we sought to investigate the usefulness of UBT without 13C-labelled external urea to detect H. pylori infection. The analysis was performed in a series of adult patients just before upper gastrointestinal endoscopy and biopsy to investigate dyspeptic symptoms. Breath samples were analyzed using isotope ratio mass spectrometry (IRMS). The natural variation of 13C and 18O isotopic abundance in the breath samples was also investigated. The results of the isotopic analysis were compared with the findings of the histopathological evaluation of gastric biopsies, which is the gold standard to detect H. pylori infection. No differences between patients with or without H. pylori infection could be detected by the isotope analysis of breath tests without 13C-urea. Therefore, our results showed that UBT without 13C-urea, analyzed by IRMS, was not useful to detect H. pylori infection in the study population.
Keywords: Helicobacter pylori; Isotope ratio mass spectrometry; Non-invasive diagnosis; Urea breath test